Psychological distress among healthcare students in Poland from COVID-19 to war on Ukraine: a cross-sectional exploratory study - Hisato, Tomomi; Nandy, Shreya; Monga, Eman M.; Sytek, Paulina; Abouzid, Mohamed; Ahmed, Alhassan Ali (Frontiers in Public Health, 2023)
Objectives Healthcare students went through a rough time in March 2022 due to extreme changes in the educational system (moving from online to stationary learning) and Ukrainian-Russian war circumstances. Our study aims to update knowledge about psychological distress and its impact on healthcare students in Poland after two years of the COVID-19 pandemic, followed by intense and political instability in Europe. Methods We conducted a cross-sectional study on healthcare students from Poznan University of Medical Sciences, Poland, from March to April 2022. The questionnaire included subjective retrospective 5-point Likert-scales ratings of anxiety, stress, and depression and self-reported information on various psychological distress predictors. Results The anxiety levels at the beginning of the COVID-19 pandemic were higher than in April 2022. There was no significant reduction in stress and depression. Females had higher initial anxiety levels than post-pandemic levels. Higher reported levels of anxiety, stress, and depression were significantly correlated with political instability in Eastern Europe (Spearman ranxiety = 0.178, rstress = 0.169, rdepression = 0.154, p ≤ 0.001, respectively). The concern about moving towards online education showed a significant association only with stress level (rstress = 0.099, p = 0.034). We also observed a positive correlation between anxiety, stress, and depression and deteriorating sleep quality (Spearman ranxiety,=0.325, rstress = 0.410, rdepression = 0.440, p < 0.001), the feeling of worsening relationships with family and peers (ranxiety = 0.325, rstress = 0.343, rdepression = 0.379, p < 0.001), and the sense of loss of efficient time management (ranxiety = 0.321, rstress = 0.345, rdepression = 0.410, p < 0.001). Conclusion Throughout the progression of the Ukrainian war and the COVID-19 pandemic, females reported improved (lower levels) levels of anxiety. Nevertheless, the current levels of self-reported anxiety post-pandemic remain alarming, while stress and depression levels remained unchanged. Mental, psychological, and social support activities are required for healthcare students, especially those away from their families. Time management, academic performance, and coping skills in relation to the additional stressors of war and the global pandemic require further research in this group of students.